Formulation and Evaluation of pH and Enzyme - dependent Metronidazole Tablet for Colon Targeted Drug Delivery System - Ippalwad, Shruti; Shinde, Jitendra; Bhosale, Ashok (Journal of Neonatal Surgery, 2025)
In this study the formulation of safe and effective Ph and Enzyme dependent coated tablet of Metronidazole was prepared for the effectual treatment of Amoebic Dysentery, Inflammatory bowel diseases. Wet granulation method is used for the formulation of colon targeted pH and Enzyme dependent coated tablet of Metronidazole. Eudragit s-100, HPMCK 4M, Guar gum polymer and Eudragit s100 (pH dependent) This coating material is used for this tablet. This coated tablet evaluated for properties such as average weight, hardness and coat thickness, disintegration, drug content. The produced tablets were subjected to in vitro release experiments for two hr at 100 rpm using 0.1 N HCl and phosphate buffer 6.8 pH for three to five hr. After that 7.4pH phosphate buffer was used and the process was repeated for 24hr. Every formulation’s % weight variation, percentage friability and drug molecule content fall within the bounds set by the united states pharmacopoeia (USP). According to the results, metronidazole would be a promising formulation to accomplish the goal of curing inflammatory bowel disorders and amoebic dysentery without causing any gastric irritation. This would be beneficial for individuals who have a history of ulcerative colitis.